Pendidikan Nilai dalam Pendidikan Kewarganergaraan Berbasis Habituasi - Resty, Muthia; Ndona, Yakobus; Saragi, Daulat (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to examine the effectiveness of value education in habituation-based Civic Education (PKn) subjects at the elementary school level. The background of the research departs from the urgent need to internalize character values in students, not only in the form of cognitive understanding, but also in real behavior that is manifested through the habituation process. The research uses a quantitative method with an observational approach. The subject of the study was 35 students in grade V of SD Negeri 132410 Tanjungbalai. The research instrument is in the form of observation sheets developed based on three main indicators, namely responsibility, discipline, and cooperation. The data obtained were analyzed using descriptive statistical techniques in the form of percentages and average values. The results of the study showed that the achievement rate of value implementation was in the high category, with an average of 81.9%. These findings confirm that habituation strategies that include daily practice, teacher examples, and strengthening attitudes through routine school activities are able to support the internalization of student character values effectively. The implications of this study recommend that habituation practices be systematically integrated into the PKn curriculum as an alternative strategy in strengthening character education, so that PKn learning is not only limited to knowledge transfer, but also a means of forming real civic behavior.